Closing the knowledge gap in pelvic neuroanatomy: assessment of a cadaveric training program - Ioana Marcu; Adrian Balica; Jeffrey A. Gavard; Eugen C. Campian; Gustavo Leme Fernandes; M. Jonathon Solnik; Vadim Morozov; Nucelio Lemos (BMC Medical Education, 2021)
Abstract Background The objective of this study is to characterize participants in a laparoscopic cadaveric neuroanatomy course and assess knowledge of pelvic neuroanatomy before and after this course. Methods This is a survey-based cohort study with a setting in a university educational facility. The participants are surgeons in a multiday laparoscopic cadaveric pelvic neuroanatomy course. Participants completed a precourse survey, including demographics and comfort with laparoscopic surgery. They then completed an identical precourse and postcourse anatomic knowledge test. Main outcomes are scores on the anatomic knowledge test precourse and postcourse. Results 44 respondents were included: 25 completed fellowship, 15 completed residency, 2 were residents, and 2 were fellows. Participants were on average 11.09 years post training, with an average of 8.67 years from training if they completed fellowship and 18.62 years if they completed residency only. 22 of 42 respondents strongly agreed or agreed they are comfortable performing complex laparoscopic hysterectomies. The average precourse score was 32.18/50 points and the mean difference score (MDS, defined as mean of Postcourse scores minus Precourse scores) was 9.80, showing significant improvement (p <  0.001). Precourse and MDS scores were not significantly different when comparing country of practice, level of training, or time since training. Conclusion Baseline knowledge of pelvic neuroanatomy was similar among groups when comparing fellowship status, place of training, or time since training. There was significant improvement in knowledge after training in this dissection method. This course garnered interest from surgeons with broad training backgrounds.